Solvent-Tuned Plasticity for Various Binder-Free Applications of a New Lead-Free Manganese Halide - Han, Joo Hyeong; Seo, Jeong Min; Choi, San Ha; Noh, Jae Geon; Min, Jeong Wan; Kim, Yu Ri; Kim, Hyeon Woo; Cho, Sung Beom; Cha, Bo Kyung; Im, Won Bin (Advanced Materials, 2025)
The development of efficient color conversion layers for μ-LED technology faces significant challenges owing to the limitations of materials that require binders. Binders are typically used to ensure uniform film formation in color-conversion layers, but they often cause optical losses, increase layer thickness, and introduce long-term stability issues. To address the limitations of materials requiring binders, cyclopropyltriphenylphosphonium manganese tetrabromide (CPTP2MnBr4) is synthesized, a novel lead-free metal halide. CPTP2MnBr4 exhibits unique solvent-based plasticity, which enables the formation of uniform films thinner than those formed with binders without the need for either heat treatment or binders. This approach eliminates the performance degradation typically associated with conventional binder systems such as optical losses and stability issues. Structural and optical analyses confirm its high luminescence efficiency and stability, supporting its potential applications in luminescent clays, direct ink writing, pattern printing, and ink drawing. Moreover, its successful application in white light-emitting diodes (WLEDs) and scintillators demonstrates that CPTP2MnBr4 can replace traditional binder systems, offering a solution to overcome the technical challenges in next-generation displays, lighting, and scintillator technologies.
Keywords: Color conversions; Color-conversion LED; Conversion layers; Free metals; Lead-Free; Lead-free metal halide; Optical-; Solvent based; Solvent-based plasticity; Uniform films; color-conversion LED; lead-free metal halide; scintillator; solvent-based plasticity